User's Perception of Public Space at Malioboro Street After Revitalization using Placemaking Approach - Marinda Noor Fajrina Noviana Putri; Syam Rachma Marcillia (Built Environment Studies, 2022)
Public open space has functioned as a development image and livability of a city. Malioboro is the most famous street in Yogyakarta with various activities and users. Malioboro street is a corridor that has been revitalized. One of the revitalization purposes is developing a public space that should accommodate all users with their activities. This research will be concentrated on the revitalization of Malioboro as a public space. Placemaking is used as an approach to find out the process of forming public space that has already formed at Malioboro street after the revitalization. So, the research aims to find out that process. The method is quantitative approach, which is a questionnaire to know the user's perception (merchant, tourism, and communities) of the placemaking. Aspects of placemaking are from Project of Public Space (PPS) with four variables: uses and activity, comfort and image, access and linkage, and sociability. Furthermore, the data will be analyzed to find out the placemaking process. The result of this research will be how far the process of the public space that occurred in the revitalized Malioboro street.